Impact of obesity and diabetes on the incidence of kidney and bladder cancers: a nationwide cohort study. Issue 5 (November 2019) - Ko, Seung Hyun; Han, Kyung Do; Yun, Jae Seung; Chung, Sungjin; Koh, Eun Sil
Abstract : Objective: Obesity and type 2 diabetes are becoming increasingly prevalent worldwide and are both associated with the increased incidence of kidney and bladder cancers. However, previous reports have provided conflicting results. We investigated the impact of body mass index (BMI) and diabetes on the incidence of both cancers in the general population. Methods: Using nationally representative data from the Korean National Health Insurance System, 9, 777, 133 subjects without any malignancy who underwent health examinations in 2009 were followed to the end of 2017. Results: After a median follow-up period of 8.32 years, 12, 544 incidents of kidney cancer and 15, 137 incidents of bladder cancer were identified. The hazard ratio (HR) for kidney cancer was the lowest in people with a BMI <18.5 kg/m 2 (HR: 0.82, 95% confidence interval (CI): 0.72–0.94) and the highest in those with a BMI ≥30 kg/m 2 (HR: 1.71, 95% CI: 1.57–1.87) compared to a reference BMI group (18.5–23 kg/m 2 ). In subjects with diabetes, obesity was associated with increased risk of kidney cancer, although the HRs were lower than observed in those without diabetes. Otherwise, there was a reduction in risk of bladder cancer with obesity in men and the HR for bladder cancer was not affected by BMI increase in women. There was a strongly positive association between diabetes and bladder cancer in the total study population. Conclusions: Obesity was a strong risk factors for kidney cancer, whereas the association between obesity and bladder cancer differed by gender. The subjects with diabetes had a higher risk for both cancers than those without diabetes.